Does origin of article impact citation metrics in Gynecologic Oncology? - Logan Corey; Christopher Walker; Alex Corey; Jonathan Konel; Ali Khalil; Hyejeong Jang; Seongho Kim; Radhika Gogoi (Elsevier, 2022)
Objectives: To determine if the origin of article published in Gynecologic Oncology ("Journal") is correlated with quality of the article when measured per US institution and per country, using an index of citation (IOC) metric as a stand-in for article quality. Methods: PubMed was used to query the Journal from 2005 to 2020. Articles not deemed original research were excluded. A US-only cohort ("US-Only") was evaluated separately from the entire cohort ("Whole"). The IOC for each article was calculated by dividing the number of citations listed in PubMed by the days from the publication date to 9/1/2021. The IOC per US institution was summarized by the median value. All articles were hand reviewed for correctness. The Whole cohort included all countries with 3 or more publications (including all of the US-Only cohort) and underwent similar analysis. Correlation coefficients were estimated using Pearson's correlation after log-transformation. Results: In the US-only cohort, 2733 articles from 276 institutions within the US contributed original articles to the Journal. The association between the number of publications per institution and the median IOC was not well correlated (Pearson's Correlation coeffeicient r = 0.16, p = 0.009). In the Whole cohort, 5,848 original research articles were published from 40 countries. There was no difference between median IOC for articles from US compared to non-US institutions was (0.0026 vs 0.0027, p = 0.287). The US median IOC was ranked 17/40. The US accounted for just over half (51.2%) of publications, and there was a trend of decreasing Non-US publications over time (p = 0.0004). Conclusions: The Journal was fairly consistent in the quality of articles published over the 15-year study period when using the IOC as a surrogate for quality, regardless of the article's country or US institution of origin.